Spectroscopic characterisation of crusts interstratified with prehistoric paintings preserved in open‐air rock art shelters1. (3rd July 2014) - Hernanz, Antonio; Ruiz‐López, Juan F.; Madariaga, Juan Manuel; Gavrilenko, Egor; Maguregui, Maite; Fdez‐Ortiz de Vallejuelo, Silvia; Martínez‐Arkarazo, Irantzu; Alloza‐Izquierdo, Ramiro; Baldellou‐Martínez, Vicente; Viñas‐Vallverdú, Ramón; Rubio i Mora, Albert; Pitarch, Àfrica; et al.
<x xml:space="preserve">Abstract</x> In situ micro‐Raman spectroscopy (μ‐RS) of rock art paintings in open‐air rock shelters entails several difficulties: sunlight, wind, dust and crusts that mask Raman signals from the pigments and any other component of the paint recipe. These problems have been considered in the present work. Special attention has been devoted to the presence of crusts. Five rock art sites in the eastern Iberian Peninsula with outstanding difficulties to be analysed by this technique have been the object of this study. In situ energy dispersive X‐ray fluorescence and diffuse reflectance infrared Fourier transform spectroscopy using portable instruments have provided important help. Moreover, microstratigraphic studies by μ‐RS and scanning electronic microscopy combined with energy dispersive X‐ray spectroscopy of micro‐specimens from the painting panels have revealed the distribution of the different components. Dolomite and calcite are dominant minerals in the rock substrata. Whewellite, gypsum, calcite, clay, dolomite, α‐quartz, anatase and haematite have been found on the surface of the painting panels or forming stratified layers in the crusts. Haematite and amorphous carbon have been detected in red and black pictographs, respectively. Copyright © 2014 John Wiley & Sons, Ltd.